Factors that determines investment based Fintech crowd funding in Malaysia - Abdul Razak, Dzuljastri; Ismail, Iliyas; Othman, Anwar Hasan Abdullah; SIDIKI, Sylla; ZULM, Syamsu Rizal (2020)
Crowd funding as a means for investment using fintech is relatively new. The popularity of venture capital and angel financing as a source of funds for businesses has decreased due the advent of fintech. The services provided are similar to the traditional finance such as simple transactions to payments, brokering and risk management. However, entrepreneurs and project owners are linked to investors by means of digitalization platforms which enable greater participation in sourcing for capital. The purpose for this research is to find factors that determine investment using crowd funding in Malaysia using Technology Acceptance Model (TAM) as its based theory. Four variables are used as measurements namely perceived informativeness, network externality, return on investment and platform quality. Data will be collected by means of questionnaires to investigate the validity of the proposed model. SPSS will be used to analyze the data collected using reliability, correlation and multiple regressions. The result will contribute to the body of knowledge in this emerging area. It will also enable practitioners to determine the significant variables that influence the willingness of customers to place funds via investment based fintech crowd funding platforms.